Gray Matter Correlates of Creativity in Musical Improvisation - Arkin, Cameron; Przysinda, Emily; Pfeifer, Charles W.; Zeng, Tima; Loui, Psyche (Frontiers in Human Neuroscience, 2019)
Creativity has been defined as requiring both novelty and effectiveness, but little is known about how this standard definition applies in music. Here we present results from a pilot study in which we combine behavioral testing in musical improvisation and structural neuroimaging to relate brain structure to performance in a creative musical improvisation task. Thirty-eight subjects completed a novel improvisation continuation task and underwent T1 MRI. Recorded performances were rated by expert jazz instructors for creativity. Voxel-based morphometric analyses on T1 data showed that creativity ratings were negatively associated with grey matter volume in the right inferior temporal gyrus and bilateral hippocampus. The duration of improvisation training, which was significantly correlated with creativity ratings, was negatively associated with grey matter volume in the rolandic operculum. Together, results show that musical improvisation ability and training are associated with grey matter volume in regions that are previously linked to learning and memory formation, perceptual categorization, and sensory integration. The present study takes a first step towards understanding the neuroanatomical basis of musical creativity by relating creative musical improvisation to individual differences in grey matter structure.